Constitutionalism: institutional guarantees of the interrelation between law and power - Gracheva, Svetlana A. (Journal of the Belarusian State University. Law, 2024)
The article is devoted to understanding of constitutionalism through institutional guarantees of the relationship between law and power, the consideration of which in the doctrine is underestimated from the point of view of conceptualising formulas of control and checking in the mechanism of power based on law. Meanwhile, the evolution of such controls indicates the dynamics of the relationship between law and power in favour of increasing the role of law while expanding its functionality, allowing us to look at law more broadly than just from the position of acts of state rule-making. The purpose of the work is to substantiate options for conceptualising the guarantees of the relationship between law and po wer taking into account formulas of control and checking as contributing to strengthen or weaken the impact of law on power relations, which also shows the type of constitutionalism (classical, post-classical, non-classical). The results of the study also consist in highlighting the direction of non-classical conceptualisation of the formula of control and checking in the mechanism of power that characterises existing legal jurisdictions – this is the model for control the execution and application of legislation as a reflection of the impact of law on power at a certain stage of the legal process.